The armed oncolytic adenovirus ZD55-IL-24 eradicates melanoma by turning the tumor cells from the self-state into the nonself-state besides direct killing - Hu, Hai-Jun (Cell Death Dis, 2020)
ZD55-IL-24 is similar but superior to the oncolytic adenovirus ONYX-015, yet the exact mechanism underlying the observed therapeutic effect is still not well understood. Here we sought to elucidate the underlying antitumor mechanism of ZD55-IL-24 in both immunocompetent and immunocompromised mouse model. We find that ZD55-IL-24 eradicates established melanoma in B16-bearing immunocompetent mouse model not through the classic direct killing pathway, but mainly through the indirect pathway of inducing systemic antitumor immunity. Inconsistent with the current prevailing view, our further results suggest that ZD55-IL-24 can induce antitumor immunity in B16-bearing immunocompetent mouse model in fact not due to its ability to lyse tumor cells and release the essential elements, such as tumor-associated antigens (TAAs), but due to its ability to put a “nonself” label in tumor cells and then turn the tumor cells from the “self” state into the “nonself” state without tumor cell death. The observed anti-melanoma efficacy of ZD55-IL-24 in B16-bearing immunocompetent mouse model was practically caused only by the viral vector. In addition, we also notice that ZD55-IL-24 can inhibit tumor growth in B16-bearing immunocompetent mouse model through inhibiting angiogenesis, despite it plays only a minor role. In contrast to B16-bearing immunocompetent mouse model, ZD55-IL-24 eliminates established melanoma in A375-bearing immunocompromised mouse model mainly through the classic direct killing pathway, but not through the antitumor immunity pathway and anti-angiogenesis pathway. These findings let us know ZD55-IL-24 more comprehensive and profound, and provide a sounder theoretical foundation for its future modification and drug development.